DEVELOPMENT OF CENTRIFUGAL ADDITIVE MANUFACTURING TECHNOLOGIES USING FINE POWDER - Berkinova, Zhazira (Nazarbayev University School of Engineering and Digital Sciences, 2025)
Powder-based Additive Manufacturing (AM) processes offer the potential to fabricate complex 3D components with high precision. The quality and performance of printed components are strongly influenced by powder characteristics, laser operating parameters, and the thermal behavior of a powder bed during the melting process. Specifically, powder characteristics such as size, shape, and size distribution play a critical role by affecting powder flowability, spreadability, and compactability. Due to the high cost of producing uniformly sized spherical metal powders, commercially available feedstocks often exhibit varied sizes and shapes. This makes powder mixing a critical pre-processing step in AM to prevent particle segregation and ensure uniform layer deposition. However, limited understanding exists regarding the flow and mixing behavior of irregularly shaped particles. To address this, the first part of the thesis investigated the mixing behavior and flowability of differently shaped powders in a rotating drum using experiments and Discrete Element Method (DEM) simulations at various rotational speeds. The obtained results demonstrated that the mixing rate constant increased notably from 10 to 50 rpm, with only slight improvement at 60 rpm. Beyond 60 rpm, mixing efficiency declined due to a shift in flow regimes. Despite a minor mixing rate gain at 60 rpm, the highest packing fraction was observed at 50 rpm, identifying it as the optimal speed for effective mixing of differently shaped powders. Powder size and geometry have a strong influence on powder distribution and packing fraction within the layer in additive manufacturing. Fine powders (d50<20 μm) offer improved melt track stability and fabricated component precision. However, fine particles often exhibit poor flowability and spreadability due to their high surface area and cohesive forces, leading to agglomeration and uneven spreading. To address these issues, the second part of the thesis introduced a novel compaction method for fine particles using centrifuge-assisted artificial high gravity. The fine powder bed compaction was analyzed employing lab-scale and large-scale centrifuge machines along with DEM simulations. The results demonstrated that artificial gravity significantly improves fine powder bed compaction in AM. DEM simulations showed an 82.8% rise in packing fraction at 71.7G compared to 1G, with rapid densification occurring within the first two rotations. Moreover, the components fabricated via laser melting under artificial high gravity exhibited reduced defects, confirming the benefits of this compaction method. Furthermore, this PhD thesis analyzed the temperature distribution within the melt pool using the newly developed analytical approach based on a disk-shaped heat source by integrating both point and doublet sources. The proposed approach incorporated heat losses due to conduction, convection, and radiation, in addition to simulating the Marangoni effect. Model validation against numerical data demonstrated excellent predictive accuracy, with over 99% agreement for the peak temperature at the top surface of the AlSi10Mg powder bed. Furthermore, validation against experimental data confirmed the reliability of the model, yielding melt pool width and depth accuracies of 94.6% and 88.1% for AlSi10Mg, and 94.5% and 85.3% for Inconel 625, respectively. Parametric studies reveal that increasing laser power from 150 W to 200 W significantly enlarges the melt pool, with maximum depth rising from 22 µm to 32 µm, indicating full powder bed penetration, thus enhancing the interlayer bonding. The final part examined how artificial gravity influences melt pool formation during laser melting. Volume of fluid simulations revealed that improved powder bed compaction achieved under high gravity conditions resulted in a 25.6% increase in melt pool depth, accompanied by a reduction in melt pool width. At elevated gravity levels, fluid motion shifted from primarily horizontal flow to a downward vertical direction, enhancing the depth of molten material penetration while limiting its lateral expansion. Under 1G, poor compaction led to void-induced balling and surface irregularities. In contrast, artificial high gravity smoothed the melt pool’s top surface. This thesis explores using gravitational acceleration to address compaction challenges with fine and potentially ultra-fine particles, thus expanding their applicability in additive manufacturing. This approach also provides a promising strategy to overcome microgravity limitations, making additive manufacturing processes feasible in space.
Keywords: Additive Manufacturing; Selective Laser Melting; Artificial High Gravity; Fine Powder Bed Compaction; Discrete Element Method; type of access: embargo